ASSOCIATION OF LOW GFR AND NON-ALCOHOLIC HEPATOSTEATOSIS ON FIBROSCAN OF LIVER - Khurram Baqai,; Mahvesh Mahmud,; Anwar, Maryam; Shoukat Ali Samejo,; Nida Hussain ,; Ambreen Wasim, (Journal of Ayub Medical College Abbottabad, 2023)
Background: Chronic kidney disease (CKD) and nonalcoholic fatty liver disease (NAFLD) are becoming a health concern, owing to their increasing incidence and prevalence. Both entities are linked to poor outcomes and increased costs, hence greatly impacting the healthcare system and economy. Therefore, it is imperative to establish the link between the two, so as to prevent disease progression and complications. Methods: The study was an observational retrospective study done in Karachi, from November 2021 to May 2022. It was conducted on 255 patients who were diagnosed with NAFLD, and the presence of CKD was then determined by calculating their GFRs. Results: Out of the 255 patients diagnosed with hepatosteatosis, 76% had a normal GFR, 20% had a mild decrease and 4% were noted to have a moderate reduction in their GFR. When cross-tabulated with CAP score, it was found that 28% had S1 grade steatosis, out of which 85% had a normal GFR, 13% had a mild decrease and 2% had a moderate decrease in GFR. 22% had S2 grade steatosis, out of which 76% had a normal GFR, 18% had a mild decrease and 6% had a moderate reduction in GFR. 50% patients had S3 grade steatosis, out of which 70% had a normal GFR, 25% had a mild decrease and 5% had a moderate reduction in GFR. Conclusion: There is an association present between NAFLD and the development of low GFR. Therefore, it is important that patients diagnosed with NAFLD are regularly screened for CKD, so as to prevent its development and complications.